Emancypacja osób autystycznych. Wprowadzenie do zagadnienia - Buława-Halasz, Joanna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2015)
This text is an attempt to introduce the issue of the emancipation of autistic people. Autism spectrum disorders are a very heterogeneous category, and a person with such a diagnosis is achieved will vary in the degree of functioning due to the symp-toms and frequently co-morbid physical difficulties and/or mental and intellectual disability. Many examples of people with high functioning autism shows that this group is strongly working for independent living and self determination. The emancipation of autistic people understood in this way goes in different directions - from raise awareness about autism to self-advocacy.